2012
DOI: 10.4049/jimmunol.1101954
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D Receptor Gene Polymorphisms and HLA DRB1*04 Cosegregation in Saudi Type 2 Diabetes Patients

Abstract: The vitamin D receptor (VDR) gene has been involved in the modulation of susceptibility to inflammatory and autoimmune conditions, and could play a role in the pathogenesis of type 2 diabetes mellitus (T2DM). Susceptibility to T2DM was recently also suggested to associate with HLA alleles. We evaluated possible correlations between VDR polymorphisms, HLA alleles, and risk for development of T2DM by analyzing 627 individuals (368 T2DM patients and 259 healthy control subjects) part of a well-characterized cohor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
35
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(37 citation statements)
references
References 54 publications
(65 reference statements)
2
35
0
Order By: Relevance
“…Serum-ionized calcium and lipid profile decreased but not significantly in TC, TG, and LDL-C. All serum vitamin D levels were significantly lower in individuals with diabetic type 2 when compared to the controls as seen in Tables 2 and 3. There is no large scaled epid emiology study evaluating vitamin D deficiency in T2DM; however, several studies of different races have reported a high prevalence of hypo-vitaminosis D in patients with T2DM [27,28]. The distribution of vitamin D status in this study sample is very much in line with the study of 29 which found up to 98 percent of the subjects had vitamin D insufficiency or deficiency.…”
Section: Resultssupporting
confidence: 85%
“…Serum-ionized calcium and lipid profile decreased but not significantly in TC, TG, and LDL-C. All serum vitamin D levels were significantly lower in individuals with diabetic type 2 when compared to the controls as seen in Tables 2 and 3. There is no large scaled epid emiology study evaluating vitamin D deficiency in T2DM; however, several studies of different races have reported a high prevalence of hypo-vitaminosis D in patients with T2DM [27,28]. The distribution of vitamin D status in this study sample is very much in line with the study of 29 which found up to 98 percent of the subjects had vitamin D insufficiency or deficiency.…”
Section: Resultssupporting
confidence: 85%
“…It has been convincingly shown that the vitamin D/VDR axis modulates the activity of the immune system, and that in turn the immune system plays a pivotal role in vitamin D metabolism [20], [21]. Different reports suggest that chronic inflammation is a key marker of obesity, the origin of inflammation during obesity and the underlying molecular mechanisms that explain its occurrence are nevertheless not fully understood.…”
Section: Discussionmentioning
confidence: 99%
“…The latter molecule increases the uptake of glucose in muscle and adipose tissue, whereas GLP-1 decreases glucagon production and increases the production of insulin in the pancreas. In addition, SCFAs possess the capacity to decrease gluconeogenesis in the liver by increasing the phosphorylation and activity of AMPK receptor (VDR) being a critical element in increased disease susceptibility [198]. It is, however, of interest that these authors reported VDR polymorphisms to be correlated with HLA-DRB1*04 and with metabolic and immunologic parameters [198] as reduced SCFAs would likely compound this association.…”
Section: Increased Intestinal Permeability In Patients With Type 2 DImentioning
confidence: 97%